Advancement in Determination of Phthalate Metabolites by Gas Chromatography Eliminating Derivatization Step - Tankiewicz, Maciej; Olkowska, Ewa; Berg, Andrzej; Wolska, Lidia (Frontiers in Chemistry, 2020)
A gas chromatography-mass spectrometry (GC–MS) method to determine polar and thermally unstable phthalate metabolites (monomethyl phthalate - MMP, monoethyl phthalate - MEP, mono-n-butyl phthalate - MnBP, mono-(2-ethylhexyl) phthalate - MEHP) has been developed. This is the first report presenting the separation of monophthalates without derivatization step and any additional equipment or special injection port. Injection parameters (temperature, pressure, time and volume of injection), chromatographic separation (retention gap, temperature program) and MS detection/identification (working parameters, ion selection) were investigated. Mechanisms and phenomena occurring under different conditions in the GC injector were evaluated and discussed. The limits of detection (LODs) of MMP, MEP, MnBP, MEHP in the protocol were 0.049, 0.036, 0.038 and 0.029 ng (per 2 µL of injection), respectively. The response of the monophthalates was found to be linear in the tested concentration range (for MMP: 0.15 – 100 ng, MEP and MnBP: 0.11 – 100 ng, MEHP: 0.087 – 100 ng per 2 µL) with the coefficient of determination higher than 0.9817 and inter-day precision in the range of 1.4 – 5.4 %. The developed method is fast, easy and repeatable. Moreover, allows for the elimination of derivatization agents, reduction of toxic waste production and simplification of analytical procedure.